Increased Loss Aversion in Unmedicated Patients with Obsessive–Compulsive Disorder - Sip, Kamila E.; Gonzalez, Richard; Taylor, Stephan F.; Stern, Emily R. (Frontiers in Psychiatry, 2018)
Introduction: Obsessive-compulsive disorder (OCD) patients show abnormalities in decision-making and, clinically, appear to show heightened sensitivity to potential negative outcomes. Despite the importance of these cognitive processes in OCD, few studies have examined the disorder within an economic decision-making framework. Here we investigated loss aversion, a key construct in prospect theory that describes the tendency for individuals to be more sensitive to potential losses than gains when making decisions. Methods: Across two study sites, groups of unmedicated OCD patients (n=14), medicated OCD patients (n=29), and healthy controls (n=34) accepted or rejected a series of 50/50 gambles containing varying loss/gain values. Loss aversion was calculated as the ratio of the likelihood of rejecting a gamble with increasing potential losses to the likelihood of accepting a gamble with increasing potential gains. Decision times to accept or reject were also examined and correlated with loss aversion. Results: Unmedicated OCD patients exhibited significantly more loss aversion compared to medicated OCD or controls, an effect that was replicated across both sites and remained significant even after controlling for OCD symptom severity, trait anxiety, and sex. Post-hoc analyses further indicated that unmedicated patients’ increased likelihood to reject a gamble as its loss value increased could not be explained solely by greater risk aversion among patients. Unmedicated patients were also slower to accept than reject gambles, effects that were not found in the other two groups. Loss aversion was correlated with decision times in unmedicated patients but not in the other two groups. Discussion: These data identify abnormalities of decision-making in a subgroup of OCD patients not taking psychotropic medication. The findings help elucidate the cognitive mechanisms of the disorder, and suggest that future treatments could aim to target abnormalities of loss/gain processing during decision-making in this population.